Can the Open Stance Forehand Increase the Risk of Hip Injuries in Tennis Players?. Issue 12 (11th December 2020) - Martin, Caroline; Sorel, Anthony; Touzard, Pierre; Bideau, Benoit; Gaborit, Ronan; DeGroot, Hugo; Kulpa, Richard
Background: The open stance forehand has been hypothesized by tennis experts (coaches, scientists, and clinicians) to be more traumatic than the neutral stance forehand as regards hip injuries in tennis. However, the influence of the forehand stance (open or neutral) on hip kinematics and loading has not been assessed. Purpose: To compare the kinematics and kinetics at the hip joint during 3 common forehand stances (attacking neutral stance [ANS], attacking open stance [AOS], defensive open stance [DOS]) in advanced tennis players to determine whether the open stance forehand induces higher hip loading. Study Design: Descriptive laboratory study. Methods: The ANS, AOS, and DOS forehand strokes of 8 advanced right-handed tennis players were recorded with an optoelectronic motion capture system. The flexion-extension, abduction-adduction, and external-internal rotation angles as well as intersegmental forces and torques of the right hip were calculated using inverse dynamics. Results: The DOS demonstrated significantly higher values than both the ANS and AOS for anterior ( P < .001), medial ( P < .001), and distractive ( P < .001) forces as well as extension ( P = .004), abduction ( P < .001), and external rotation ( P < .001) torques. The AOS showed higher distractive forces than the ANS ( P = .048). The DOS showed more extreme angles of hip flexion ( P < .001), abduction ( P < .001), and external rotation ( P = .010). Conclusion: The findings of this study imply that the DOS increased hip joint angles and loading, thus potentially increasing the risk of hip overuse injuries. The DOS-induced hip motion could put players at a higher risk of posterior-superior hip impingement compared with the ANS and AOS. Clinical Relevance: Coaches and clinicians with players who have experienced hip pain or sustained injuries should encourage them to use a more neutral stance and develop a more aggressive playing style to avoid the DOS, during which hip motion and loading are more extreme.